2023
DOI: 10.7554/elife.89136.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lactate transporter MCT1 in hepatic stellate cells promotes fibrotic collagen expression in nonalcoholic steatohepatitis

Kyounghee Min,
Batuhan Yenilmez,
Mark Kelly
et al.

Abstract: Circulating lactate is a fuel source for liver metabolism but may exacerbate metabolic diseases such as nonalcoholic steatohepatitis (NASH). Indeed, haploinsufficiency of lactate transporter monocarboxylate transporter 1 (MCT1) in mice reportedly promotes resistance to hepatic steatosis and inflammation. Here, we used adeno-associated virus (AAV) vectors to deliver thyroxin binding globulin (TBG)-Cre or lecithin-retinol acyltransferase (Lrat)-Cre to MCT1fl/fl mice on a choline deficient, high fat NASH diet to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Dgat2 mRNA was not affected in FASNKO groups in which sdDgat2 was not administered. In a separate study, we confirmed that the AAV9-LRAT-Cre construct efficiently and selectively depletes MCT1 in stellate cells when injected into MCT1 fl/fl mice 55 . Consistent with our previous results 24 , total liver triglycerides were significantly lowered in all sdDgat2 treated groups (Fig.…”
Section: Strikingly Fasn Inhibition Insupporting
confidence: 55%
See 1 more Smart Citation
“…Dgat2 mRNA was not affected in FASNKO groups in which sdDgat2 was not administered. In a separate study, we confirmed that the AAV9-LRAT-Cre construct efficiently and selectively depletes MCT1 in stellate cells when injected into MCT1 fl/fl mice 55 . Consistent with our previous results 24 , total liver triglycerides were significantly lowered in all sdDgat2 treated groups (Fig.…”
Section: Strikingly Fasn Inhibition Insupporting
confidence: 55%
“…AAV8-TBG-Cre and Control AAV constructs were produced by UMass Chan Viral Core, as previously described 56 . AAV9-Lrat-Cre was designed in house 55 and produced by Vector BioLabs.…”
Section: Aav Constructsmentioning
confidence: 99%